Colistin Is Extensively Lost during Standard In Vitro Experimental Conditions - Karvanen, Matti (Antimicrob Agents Chemother, 2017)
Colistin adheres to a range of materials, including plastics in labware. The loss caused by adhesion influences an array of methods detrimentally, including MIC assays and in vitro time-kill experiments. The aim of this study was to characterize the extent and time course of colistin loss in different types of laboratory materials during a simulated time-kill experiment without bacteria or plasma proteins present. Three types of commonly used large test tubes, i.e., soda-lime glass, polypropylene, and polystyrene, were studied, as well as two different polystyrene microplates and low-protein-binding microtubes. The tested concentration range was 0.125 to 8 mg/liter colistin base. Exponential one-phase and two-phase functions were fitted to the data, and the adsorption of colistin to the materials was modeled with the Langmuir adsorption model. In the large test tubes, the measured start concentrations ranged between 44 and 102% of the expected values, and after 24 h, the concentrations ranged between 8 and 90%. The half-lives of colistin loss were 0.9 to 12 h. The maximum binding capacities of the three materials ranged between 0.4 and 1.1 μg/cm(2), and the equilibrium constants ranged between 0.10 and 0.54 ml/μg. The low-protein-binding microtubes showed start concentrations between 63 and 99% and concentrations at 24 h of between 59 and 90%. In one of the microplates, the start concentrations were below the lower limit of quantification at worst. In conclusion, to minimize the effect of colistin loss due to adsorption, our study indicates that low-protein-binding polypropylene should be used when possible for measuring colistin concentrations in experimental settings, and the results discourage the use of polystyrene. Furthermore, when diluting colistin in protein-free media, the number of dilution steps should be minimized.